Kebijakan Pengelolaan Sumber Daya Informasi Perpustakaan Yang Ramah Difabel dan Inklusif - Masriyatun; Heny Perwitosari; Argyo Demartoto (Perpustakaan Universitas Riau, 2021)
Management of information resources is an important factor that must be developed in a university library that is disabled friendly and inclusive. This study aims to determine the information resource management policy at the Sebelas Maret University Library UPT that is friendly and inclusive. The method used is descriptive qualitative and quantitative methods. Conducted through interviews, documentation and questionnaires with a sample of 33 respondents. Data processing using SPSS 25. The results obtained are in determining information resource management policies for disabled users by classifying sources, source storage, systems, and search media, user and source adjustment methods, and document packaging and presentation methods. The results of the study stated that the management of library information resources at the UPT Library of UNS has a high category, this is evidenced by a number of 21 people or 63.6% of respondents claiming to be able to get information from information sources provided by the UPT Library of UNS with the website https://Library. uns.ac.id. The conclusion is that the management of information resources at UPT Sebelas Maret University Library, Surakarta, can be said to be disabled friendly and inclusive because the information sources provided can be used by non-disabled and disabled users. However, special facilities for disabled users need to be improved.